A brief study on MHD viscoelastic nanofluid flow due to variable thick surface with zero normal flux. (August 2021) - Khan, Mair; Salahuddin, T.; Elmasry, Yasser
Abstract: In this paper, numerical study of nanoparticles immersed in a viscoelastic fluid is discussed. The condition of zero normal flux is assumed which means that no mass flux exists near the variable thick surface. To control the arbitrary motion of nanoparticles, magnetic field is applied at the surface of sheet. After boundary layer, the governing partial differential equations are converted into ordinary differential equations by means of similarity transformations. The following system is calculated numerically by employing shooting method in conjunction with RK-five method. The velocity profile shows an increasing behavior for large values of α and λ. The base flow temperature profile reduces for increasing values of Pr number and N b parameter. Also, the results for skin frictions coefficient, mass and heat transport rate are explored with the help of tables. A comparative study has been made with prior published work.